2008
DOI: 10.1177/021849230801600508
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Survival in Patients after Bidirectional Glenn Shunt

Abstract: Clinical characteristics, echocardiographic values, and catheterization data of 45 patients with a functional univentricular heart who had a bidirectional Glenn shunt instituted between November 1994 and October 2006 were retrospectively reviewed. Median age at operation was 20 months (range, 9 months to 19 years). Median follow-up time after the bidirectional Glenn operation was 4 years (range, 1 day to 11 years). The early mortality rate was 4/45 (8.9%); overall mortality was 24.4%. Actuarial survival after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…BDG cavopulmonary anastomosis has several advantages, including relief of the volume load on a single functional ventricle [Kobayashi 1991;McElhinney 1998], reduced atrioventricular valve regurgitation, avoidance of PA distortion resulting from PA banding or a systemic-to-pulmonary artery shunt, reduction of ventricle size, and prevention of pulmonary vascular obstructive disease [Silvilairat 2008]. In 1991, Kobayashi et al first reported the use of BDG with an additional pulmonary blood flow in children not suitable for the Fontan procedure, which is the standard definitive palliation in such patients [Kobayashi 1991].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BDG cavopulmonary anastomosis has several advantages, including relief of the volume load on a single functional ventricle [Kobayashi 1991;McElhinney 1998], reduced atrioventricular valve regurgitation, avoidance of PA distortion resulting from PA banding or a systemic-to-pulmonary artery shunt, reduction of ventricle size, and prevention of pulmonary vascular obstructive disease [Silvilairat 2008]. In 1991, Kobayashi et al first reported the use of BDG with an additional pulmonary blood flow in children not suitable for the Fontan procedure, which is the standard definitive palliation in such patients [Kobayashi 1991].…”
Section: Discussionmentioning
confidence: 99%
“…A number of disagreements exist regarding BDG, including timing of the procedure [Silvilairat 2008] and the interval to Fontan completion. Moreover, there is contention regarding the use or elimination of accessory pulsatile forward pulmonary blood flow [Silvilairat 2008].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with isomerism will require cardiac surgery, some requiring staged surgery as they proceed along the functionally univentricular pathway. Isomerism has been noted to impact postoperative outcomes and general morbidity and mortality [9][10][11]. What has not been previously described are the characteristics of the initial birth hospitalization in those with isomerism compared to those without.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant procedures are often required at the time of BDCA to ensure optimal anatomic and physiologic conditions for completion Fontan. Prior publications have evaluated risk factors for second-stage mortality and morbidity [4,[7][8][9][10][11][12][13]. No study to date has primarily focused on the impact of pulmonary arterioplasty (PAplasty) on BDCA outcomes [4,7].…”
mentioning
confidence: 99%